2004
DOI: 10.1111/j.0030-1299.2004.12958.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of niche breadth, resource availability and range position on the life history of butterflies

Abstract: We analysed the relationship between three life history characteristics (mobility, length of flight period and body size) and niche breadth (larval host plant specificity and adult habitat breadth), resource availability (distribution and abundance of host plants) and range position (distance between the northernmost distribution record and southernmost point of Finland) of the butterfly fauna of Finland. The data is based on literature and questionnaires. Often in across species studies p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
126
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(136 citation statements)
references
References 51 publications
(67 reference statements)
5
126
2
3
Order By: Relevance
“…Furthermore, a high level of temporal fragmentation, namely short individual life span in relation to long light period, in combination with protandry seriously reduced the efective population size (sensu Lande and Barrowclough 1987;Hill 1972), thus accelerating the loss of genetic variability in small populations. In contrast to several earlier studies, which suggested that extinction risk in butterlies decreases with lengthening light period (Komonen et al 2004;Kotiaho et al 2005;Franzen and;Johannesson 2007), our analyses did not reveal any link between light period length alone and species conservation status. The most straightforward explanation for such a result could be that light period length per se is unimportant for species extinction risk, and it only matters in combination with adult longevity.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, a high level of temporal fragmentation, namely short individual life span in relation to long light period, in combination with protandry seriously reduced the efective population size (sensu Lande and Barrowclough 1987;Hill 1972), thus accelerating the loss of genetic variability in small populations. In contrast to several earlier studies, which suggested that extinction risk in butterlies decreases with lengthening light period (Komonen et al 2004;Kotiaho et al 2005;Franzen and;Johannesson 2007), our analyses did not reveal any link between light period length alone and species conservation status. The most straightforward explanation for such a result could be that light period length per se is unimportant for species extinction risk, and it only matters in combination with adult longevity.…”
Section: Discussioncontrasting
confidence: 99%
“…We used female wing span (mm) as a measure of butterfly body size, because there is a very strong positive correlation between female and male body size (22). Wing-span measurements for both sexes are based on Marttila et al (19), in which the mean of a sample of 20 individuals was given, with an exception of some rare species with fewer individuals measured.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we construct an ecological extinction risk rank to predict which species face the highest risk of becoming extinct. Our data are predominantly based on published literature (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Greenwood et al 1978;Ims 1990;Sorci et al 1994;Negro et al 1997;Massot & Clobert 2000) and winged invertebrates (e.g. Den Boer 1970;Roff 1997;Komonen et al 2004). Unlike winged arthropods, spiders (Araneae) and mites (Acaridae) often perform aerial dispersal in a predominantly uncontrolled mode (e.g.…”
mentioning
confidence: 99%